Here comes the Easter Cat - Underwood, Deborah; Rueda, Claudia (New York, NY Dial Books for Young Readers, 2014)
When Cat tries to replace the Easter Bunny, he soon learns that the job is much harder than he expected--and does not allow time for naps.
Keywords: Cats -- Fiction; Easter Bunny -- Fiction; Humorous stories